The Carry-Over of Mycotoxins in Products of Animal Origin with Special Regard to Its Implications for the European Food Safety Legislation - Schröer-Merker E; Völkel I; Czerny C-P (Scientific Research Publishing, 2011)
At present, carry-over research in mycotoxins experiences a change in focus. We reviewed the state-of-the-art knowl-edge regarding carry-over in aflatoxins, ochratoxin A, Fusarium toxins, patulin, ergot and citrinin. The common cooc-currence of mycotoxins demands for employment of multi-toxin analysis and poses a new challenge in reliable health hazard assessment. Synergies in adverse mycotoxin effects call for a revision of various guidance levels in feed. We found a lack of risk assessment regarding carry-over of rare mycotoxins and metabolites usually considered negligible.
Keywords: Carry-Over Research, Mycotoxins, Co-Occurrence, Synergistic Effects, Food Legislation, Threshold Limits, Compliance; 1001 Agricultural Biotechnology; 1111 Nutrition and Dietetics